(untitled) (Libellarium: journal for research in the field of information and related sciences, 2012)
The aim of the paper is to investigate the seized illustrative material, mostly caricatures, from satirical magazines Bič, Trn, Stršen, Tries, and Vrač pogađačduring the reign of Károly Khuen Héderváry (1883–1903). Only the illustrations that were a combination of image and text were taken into consideration. The magazines kept in the National and University Library in Zagreb were used as source materials, and the legal grounds on which the illustrations were seized were presented based on archival data from the Croatian State Archives. The first part of the paper presents the seizure of illustrations on legal grounds, and the second part discusses the multiple meanings of images in relation to text, trying to establish to what extent the caricatures and illustrations in given magazines can be viewed as carriers of polysemous messages. Although a definite conclusion on the volume and types of seizedillustrationsduring the reign of Károly Khuen Héderváry cannot be made due to inadequate sources, we could reconstruct the legislative and political context of bans and prove the power of the image, which is the basic contribution of this paper.